Sosialisasi E-Paper Analisadaily Meningkatkan Keterampilan Berpikir Kritis Masyarakat Anti Hoax - Sisi Rosida; Eka Surya Fitriani; Nurbaiti Ali (JPM: Jurnal Pengabdian Masyarakat, 2024)
The KKNT program requires thought, energy and science and technology in planning and implementing development. People are often trapped in misinformation and the source of the truth is unclear. People also don't know the importance of critical thinking, so they still put hate speech on social media. And there is no digital literacy to prevent hoax news. To overcome this problem, socialization was held which aimed to improve the critical thinking skills of the anti-hoax community. To overcome this problem, socialization was held which aimed to improve the critical thinking skills of the anti-hoax community. This Community Service is located in Suka Damai Village, where the KKNT program is implemented. The methods used in this training are lectures, discussions and demonstrations. The results of the training show that information literacy using the Analisadaily E-Paper media can be used as an alternative in improving the critical thinking skills of the anti-hoax community. Information literacy activities using the Analisadaily E-Paper which can be uploaded via digital applications have been described as citizens who can use technology and the internet effectively. This is reflected positively in avoiding inappropriate language, hate speech, and not believing in false information.